Políticas estaduais de desenvolvimento e a modernização desigual do território goiano entre as décadas de 1940 a 1980 - Gomes, Ricardo Divino de Oliveira (2024)
It is possible, based on the construction of a regional framework for the state of Goiás, in the period from the 1940s to the 1980s, to recognize a profound uneven development of the Goiás territory. This unequal regional picture manifests itself when we spatialize variables such as de-mographic distribution, urbanization rate, economic data, production systems, trade and services network, income and also in the unequal distribution of networks: rail, road and electricity. It is noteworthy that this geographically unequal development of the Goiás territory was promoted by the intense action of the State, at the federal and state levels, through public policies in different sectors that capitalized, in different ways, the territory. As an example of the role of federal and state public policies in the production of the territory of Goiás, we can mention the construction of two capitals: Goiânia and Brasília, the creation of SUDECO, the execution of the POLOCEN-TRO and PERGEB projects, in addition to the State Government Plans. Based on this recogni-tion, the general objective of the research that supported this dissertation was to investigate the processes that promoted the uneven development of the territory of Goiás between the 1940s and 1980s. The investigation brought together methodological procedures such as bibliographic review, secondary data collection, documentary research and information mapping. As a sec-ondary objective, we sought to evaluate how the actions of the National State and, above all, state policies, promoted the unequal use and occupation of the territory of Goiás. Based on these objectives, we seek to verticalize our analysis to public policies developed within the scope of state governments and how they also reinforce the unequal production of the territory of Goiás. Following this perspective, we seek to systematize the state political actions that reinforced un-even modernization in Goiás in the period between the 1940s and the 1980s. The option for this time frame is justified by the fact that it was during this period that federal and state policies played an intense role in the formation and uneven development of Goiás. In this way, Brazil's modernizing project led to the geographically uneven development of the territory of Goiás.